Halal values and attitude among Muslim worldwide: Does it affect the adaptation of marketing program strategy? / Hazlinda Hassan and Jamil Bojei - Hassan, Hazlinda; Bojei, Jamil (Universiti Teknologi MARA, Kedah, 2019)
The main purpose of this paper is to examine the influence of Halal values and attitude on marketing program adaptation. A self-administered survey has been distributed to a sample of 110 Malaysian Halal exporters that involved in variety of product categories. The results of SEM-PLS analysis show that Halal values and attitude have significant and positive influence on the marketing program adaptation. The study was limited to the examination of the socio-cultural factors pertinent to the Halal industry on the adaptation strategy of marketing program among Malaysian exporting firms that dealing with Halal certified products. In practice, the understanding of the role of Halal values and attitudes on marketing program adaptation will contributes to exporters and policy makers in their efforts to improve marketing effectiveness and export performance of Halal products in global Halal market through the development of product that is closely adapted to export market specificity. In theory, the investigation of standardization versus adaptation issue in Halal market has contributed to the body of knowledge of international marketing strategy by adding single industry values.